Educational Borrowing and Mathematics Curriculum: Realistic Mathematics Education in the Dutch and Indonesian Primary Curriculum - Revina, Shintia; Leung, Frederick Koon Shing (International Journal on Emerging Mathematics Education, 2018)
Since the late 1990s, Indonesian mathematics educators have considered Realistic Mathematics Education (RME), the Dutch approach to mathematics instruction, to be the basis for educational reform. In the National curriculum development, RME has, therefore, been reviewed as among the theoretical references to the curriculum goals and content. In the present study, an analysis of the consistency between RME and the curriculum descriptors and contents in Indonesia is presented. This is supplemented with some comparisons to that in the Netherlands. Findings in this study revealed that while most of RME principles are reflected in the Indonesian curriculum, the descriptions were often very general and less explicit compared to the Dutch curriculum. They were also limited by the content-based approach as well as by the centralized decision making process of the contents to be taught which have been pre-determined at the national level. This study suggests future research to see how the curriculum may influence teachersâ enactment of RME at classroom level.